Palawa Magazine as a Platform for Advocating for Victims of the 1965 Tragedy by Sekber’65 Surakarta - Berliana Mifta Azzahra; Hieronymus Purwanta (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
The 1965 Tragedy left survivors facing prolonged discrimination and limited opportunities to voice their experiences, aspirations, and demands. In this context, Palawa Magazine emerged as a community-based publication that sought to advocate for victims and preserve their collective memory. This study aims to analyze the background of the publication of Palawa Magazine by the Surakarta Joint Secretariat '65 (Sekber '65) and to examine its role as a medium of advocacy for the victims of the 1965 Tragedy. This study employs historical method encompassing heuristics, source verification, interpretation, and historiography, to reconstruct and interpret the publication of Palawa Magazine as an advocacy medium for the victims of the 1965 Tragedy. The findings reveal that Palawa Magazine was published in response to the limited space available for victims of the 1965 Tragedy to express their experiences, aspirations, and demands. As an advocacy medium, the magazine functions as a communication platform for survivors and the wider public, an educational resource on history and human rights, a means of shaping collective memory, and a medium advocating for recognition, the restoration of rights, and reconciliation for the victims of the 1965 Tragedy. Through its various sections and news coverage, Palawa Magazine contributes to raising public awareness of the importance of addressing past human rights violations and preserving the collective memory of the 1965 Tragedy. In conclusion, Palawa Magazine functioned not only as a medium for disseminating information but also as an advocacy instrument that amplified survivors' voices, strengthened collective memory, promoted public history, and encouraged a more inclusive dialogue on justice and the resolution of past human rights violations in Indonesia.